Incipient and repeatable plastic flow in incremental sheet-bulk forming of gears. Issue 9 (October 2016) - Sieczkarek, P.; Wernicke, S.; Gies, S.; Martins, P.; Tekkaya, A.
Abstract This paper analyses the differences between incipient and repeatable material flow in the incremental sheet-bulk metal forming (SBMF) of gears produced by indentation along the direction perpendicular to the sheet thickness. The underfilling of the punch cavity during the first indentation, which prevents the production of sound disk gears, is explained on the basis of constrained material flow under material strain hardening. A solution based on the utilization of a tailored disk blank is proposed to overcome this defect. The geometry of the tailored disk blank is determined by means of finite element analysis, and the overall methodology involved material characterization and experimentation with DC04 mild steel. The discussion on the extent of the plastic deformation region under constrained and free-material flow during indentation is complemented by experimental results obtained with a flat punch in rectangular sheet blanks of aluminium EN AW-1050A.